Manajemen Kesehatan Personal Hygiene Ibu Hamil - Leni Rozani; Ferasinta Ferasinta; Panzilion Panzilion (Bengkulu Institute, 2023)
Personal Hygiene needs special attention for pregnant women, the World Health Organization Indonesia (WHO Indonesia) has issued the importance of personal hygiene. Personal Hygiene for pregnant women is cleaning performed by pregnant women to reduce the possibility of infection. The purpose of this activity is to increase the knowledge and understanding of pregnant women about personal hygiene during pregnancy and to increase the awareness of pregnant women to always be able to maintain personal hygiene. Activities carried out for all pregnant women at the Susi Midwife Practice. The activity is carried out by providing education in the form of counseling using the lecture method with the help of a media projector. The time required to deliver the material is 50 minutes. There is an increase in the knowledge of pregnant women about the importance of maintaining personal hygiene during pregnancy.